THE INFLUENCE OF USING JIGSAW TECHNIQUE AND READING MOTIVATION TOWARD THE EIGHTH YEAR STUDENTS’ READING COMPREHENSION ACHIEVEMENT AT SMP PADMAJAYA PALEMBANG - Wiryadi, Wiryadi; Syahri, Indawan; Tahrun, Tahrun (Universitas Muhammadiyah Palembang, 2025)
This article was aimed to find out the significance average score and motivation between Jigsaw and Conventional Technique. Due the interpretation of this study, it found that: (1) there was a significant difference in reading achievement between the students who were taught by using Jigsaw and those are taught using conventional technique since it was found that the result was 0.024 it was lower than significant level (0.05), (2) there was significant difference in reading achievement between the students who have high motivation by using Jigsaw and conventional technique since the result was 0.002 and it means that lower than significant level (0.05), (3) there was significant difference in reading achievement between the students who have low motivation by using Jigsaw and conventional technique since the result was 0.000 and it was lower than significant level (0.05), and (4) there was an interaction effect of technique used and student’s motivation in improving reading achievement since the result of interaction effect was lower (0.042) than the significant level (0.05). Based on the result, the writer conclude that Jigsaw and motivation gave the significant influence for student’s narrative reading achievement since there was a significant improvement before and after taught Jigsaw technique.